Adaptation of Fragrant Rice in Central China to Climate Change: The Effects of Shifting Sowing Date on Yield and 2‐Acetyl‐1‐Pyrroline Content - Haiwei Zhang; Youqin Xiao; Xinyi Gu; Mingshuai Chen; Dehao Feng; Shuochen Jiang (Food and Energy Security)
ABSTRACT Adjusting the sowing date is a crucial strategy for improving rice adaptability to climate change and improving grain yield. Among the quality traits of fragrant rice, the content of 2‐Acetyl‐1‐Pyrroline (2‐AP) in brown rice has garnered significant attention due to its impact on flavor and market value. The comprehensive effects of weather changes induced by adjusting the sowing date on the synthesis and accumulation of 2‐AP in fragrant rice, as well as on yield, remain unclear. We conducted a 5‐year field study in Hubei Province, China, measuring sunshine duration, temperature, and rainfall variations under six sowing dates. The research aimed to assess the comprehensive effects of these changes on the 2‐AP content in brown rice and fragrant rice yield. Delaying the sowing date resulted in shortening the rice growth duration from transplanting to heading. Early sowing (March 16) resulted in the highest rice yield, while late sowing (June 1) led to the highest 2‐AP content. Generally, with delayed sowing, the effective panicles and 1000‐grain weight increased, while the number of spikelets per panicle and grain filling rate decreased. The contents of proline, pyrroline‐5‐carboxylic acid, and γ‐aminobutyric acid exhibited a trend of initially increasing and then decreasing with delayed sowing. The 2‐AP content was significantly positively correlated with rainfall during the grain filling to maturity stage, while it showed significant negative correlations with sunshine duration, average air temperature, and the number of high temperature days (maximum air temperature ≥ 35°C) during the same stage. Since the sowing date for the highest yield differed from that for the highest 2‐AP content, we recommend early sowing to achieve optimal yield while implementing other strategies to mitigate the negative effects of prolonged sunshine duration and high temperatures during the grain filling to maturity stage on 2‐AP content. This study reveals the relationship between 2‐AP content and the yield of fragrant rice with weather factors during different growth stages, providing new insights for adjusting sowing dates to adapt to climate change in order to achieve either high yield or high 2‐AP content.